A PRAGMATIC ANALYSIS OF PRESIDENT MUHAMMADU BUHARI’S SELECTED SPEECHES ON CLIMATE CHANGE - Tijani Tifili, Delia (International Journal of Arts, Languages, Linguistics and Literary Studies, 2023)
Appropriate language deployment aids effective communication and enhances smooth social cohesion, national development and progress; the reverse occurs when linguistic resources are poorly managed. It is to interrogate the pragmatic implications of the linguistic resources used by the Nigerian President, Muhammadu Buhari, in his selected speeches on climate change that this study sets out. To achieve this, three speeches of the President were purposively sampled between May and August, 2020. These speeches were subjected to the theoretical affordances of Jacob Mey’s (2001) Pragmatic Acts Theory. It was found that the predominant pragmeme in the corpus was that of informing. This pragmeme was expressed by means of eight (8) allopracts: Reporting, advocating, appraising, reminding, directing, assuring, asserting and appreciating. These pragmatic nuances were anchored on pragmatic strategies as Shared Situation Knowledge (SSK), Inference (INF) and Reference (REL). The study concludes that the choice of linguistic resources in the corpus was appropriate to the end that the perceived information needs of the masses seemed to be factored into the diction, as evidenced by the pragmatic strategies utilized. On the strength of this claim, the speeches were basically informative as expected of speeches delivered under similar circumstances.